Influence of plasma spraying current on the microstructural characteristics and tribological behaviour of plasma sprayed Cr2O3 coating - Odhiambo John Gerald (Elsevier, 2021)
In this study, the impact of varying spraying current on tribological performance and microstructural properties for coating was investigated. Atmospheric plasma spraying (APS) was used as the technique of depositing coatings on Q235 grade steel (equivalent to ASTM A36 mild steel). The coated samples were characterized using optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), adhesion testers and microhardness tester. Scratch tests were carried out under ambient and dry environments using a pin-on-plate configuration against Tungsten Carbide (WC) body (pin/stylus) for a constant load. It was found that samples sprayed under higher current had better adhesive bond and erosion wear resistance, they also had the lowest wear loss and least percentage porosity. Additionally, hardness was improved almost 10 times of the base material in comparison to lower current samples. Resumen: En este estudio se investigó el impacto de la corriente de pulverización variable sobre el rendimiento tribológico y las propiedades microestructurales para el recubrimiento del Cr2O3. La pulverización con plasma atmosférico (PPA) se usó como la técnica para depositar recubrimientos de Cr2O3 sobre acero de grado Q235 (equivalente al acero dulce ASTM A36). Las muestras recubiertas se caracterizaron usando microscopía óptica (MO), microscopía electrónica de barrido (MEB), espectroscopia de energía dispersiva (EED), probadores de adherencia y probadores de microdureza. Las pruebas se llevaron a cabo en medios ambientales y secos utilizando una configuración de pin en placa contra el cuerpo de carburo de tungsteno (WC) (pin/stylus) para una carga constante. Se encontró que las muestras rociadas con una corriente más alta tenían un mejor enlace adhesivo y una mejor resistencia al desgaste por erosión, también tenían menor pérdida de desgaste y menor porcentaje de porosidad. Además, se mejoró la dureza casi 10 veces del material base en comparación con muestras de corriente más baja.